Wielokulturowość organizacji. Wyzwania wobec zarządzania - Kożusznik, Barbara (Multicultural organization : challenge towards management, 2006)
The article discusses the issue of multicultural organizations and diversity management. It shows the positive relation between the diversity of organization and its effectiveness as well as satisfaction of workers and analyses the problems of the minorities in organizations. The results of empirical studies on diversity management in Poland are presented - the problems of diversity connected with Polish organizations and workers - the prejudices, weaknesses of management instruments as well as positive examples - as the satisfaction of work in multicultural organizations and example of succesful diversity project. The article underlines the using diversity as an organizational advantage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 372-380